Efektivitas Program Pembayaran Pajakelektronik (E-Billing) Dikantor Pelayanan Pajak Pratama Tampan Kota Pekanbaru - Deni Saputra; Sujianto Sujianto (Peneliti.net, 2022)
E-billing is a program carried out by the Directorate General of Taxes in the field of tax payments. Payment reform is expected to make it easier for taxpayers to make tax payments, because taxpayers do not need to come to the tax office. The theory used in this study is the effectiveness theory of Campbell (1989) in Mutiarin (2014) with 5 (five) indicators: Program Success, Target Success, Program Satisfaction, Output and Input Levels, Achievement of Overall Goals. The purpose of this study was to determine the effectiveness of electronic tax payments (e-billing) and the inhibiting factors of the effectiveness of electronic tax payments (e-billing) at the Pekanbaru Tampan Tax Service Office. By using qualitative research methods with data collection techniques by observation, interviews, and documentation. This study resulted that electronic tax payments (e-billing) at the Pekanbaru Tampan Pratama Tax Service Office were optimally measured by 5 indicators. The inhibiting factors for the Effectiveness of Electronic Tax Payments (e-billing) at the Pekanbaru Tampan Pratama Tax Service Office are down servers, network connections and the existence of technology gaps between taxpayers